Inertia and Switching Intention Analysis of Muslim Customers to Switch to Sharia Banks in Indonesia - Suwandi, Indra; Sobari, Nurdin (Journal of Strategic and Global Studies, 2023)
Abstract Purpose – The fact that the roles of Conventional Banking are still far dominant than Sharia Banking and keep growing show that most Muslims in Indonesia are inert to Conventional Banking. Unfortunately, research on this subject is very limited. This study aims to analyze the Inertia on Conventional Banking, and Intention to Switch to Sharia Banking of Muslim Customers. Design/methodology/approach – This is a quantitative research. Six antecedents of customer Inertia have been identified i.e.: Knowledge, Confusion, Similaritiy, Switching Costs, Satisfaction, and Religious Norms; and two antecedents of Switching Intention i.e.: Inertia and Satisfaction. 315 data from online survey were analyzed using SEM with the LISREL program, and Friedman Test with the PASW Statistics. Findings – That Knowledge and Similarities have significant negative effect; Confusion and Switching Costs have significant positive effect on customer Inertia; while Satisfaction and Religious Norms have no significant effect. Then that customer Inertia and Satisfaction have negative effect significantly on Switching Intention. Another important findings, there are significant difference of the levels of the customer Inertia, Satisfaction and Switching Intention indicators. Research limitations – provided. Practical implications – The findings are critical because provide clear directions for Sharia Banking in formulating the effective and efficient development strategy. Originality/value – This is a little of research which analyzes the inertia and intention to switch to Sharia Banking of Muslim customers in Indonesia completely. Type of paper – Research Article.